My Darling Detective - Norman, Howard (Boston : Houghton Mifflin Harcourt, 2017)
"Jacob Rigolet, soon to be fired from his position as assistant to a wealthy art collector, looks up from his seat at an auction to see his mother, Nora Ives Rigolet, until that day head librarian at Halifax Free Library, walk almost casually up the aisle and fling an open jar of black ink at master photographer Robert Capa's "Death on a Leipzig Balcony." Jacob's fiancee, the erotically accomplished Detective Martha Crauchet, is assigned to the interrogation. In My Darling Detective, Howard Norman delivers a fond and witty homage to noir, as Jacob's understanding of the man he has always assumed to be his father unravels against the darker truth of Emil Smith, a Halifax police officer suspected but never convicted of murdering two Jewish residents during the shocking upswing of anti semitism in 1945, the year Jacob was born. The denouement, involving a dire shootout and an emergency delivery--it's the second Rigolet to be born in the Halifax Free Library in a span of three decades--is Howard Norman at his "provocative...haunting"* and uncannily moving best. *(Janet Maslin, New York Times)"--
Keywords: English fiction